Serbest ticaret anlaşmaları çerçevesinde Türkiye-K.Afrika Ülkeleri ticari ilişkileri - Ada, Mustafa (My University, 2014)
Türkiye ile Avrupa Birliği (AB) arasındaki gümrük birliğini düzenleyen 1/ 95 sayılı Türkiye-AB Ortaklık Konseyinin Kararı’na istinaden, Türkiye’nin, AB Ortak Ticaret Politikası’na uyum yükümlülüğü bulunmaktadır. Bu kapsamda Türkiye, AB’nin tercihli ticaret anlaşması imzaladığı ülkelerle karşılıklı yarar esasına dayalı benzer anlaşmalar imzalamaktadır. Türkiye’nin imzalamış olduğu serbest ticaret anlaşmaları (STA) Türkiye’nin dış ticaretinde ticaret hacmini artırıcı etki yapmakta, fakat AB’nin imzaladığı, Türkiye’nin ise hala imzalayamadığı serbest ticaret anlaşmaları ise Türk dış ticaretinde haksız rekabetin oluşmasına neden olmaktadır. AB’nin imzaladığı serbest ticaret anlaşmaları sonucunda, üçüncü ülkelere uygulanan gümrüklerin kaldırılmasıyla, üçüncü tarafların malları AB üzerinden Türkiye’ye gümrüksüz girerek ticaret sapmasına neden olabilmektedir. Ayrıca, STA ile AB’nin üçüncü ülkelere vermiş olduğu tavizleri, Türkiye de Gümrük Birliği kapsamında vermekle yükümlüdür. Yeni dönemde AB'nin gerçekleştireceği STA’lar Türkiye'yi ticari açıdan daha çok rekabet baskısı altına alacak ve etkileyecektir. Türkiye, 2000’li yıllardan itibaren dış politikasındaki esaslı değişimin sonucu çok taraflı bir dış ticaret politikası takip etmeye başlamış, bu kapsamda Ortadoğu ve K. Afrika ile olan ilişkilere ayrı bir önem atfetmiştir. Çalışma kapsamında 5 Kuzey Afrika Ülkesi (Mısır, Tunus, Fas, Libya, Cezayir) ele alınmakta, Türkiye’nin bölge ülkeleri ile ticari ilişkilerine değinilerek, STA’ların genelde Türk dış ticaretine, özelde ise Türkiye ile K. Afrika ülkeleri arasındaki ticari ilişkilere etkileri değerlendirilmektedir. Bu değerlendirmeler yapılırken, Türkiye’nin bölge ülkeleri ile STA’ların yürürlüğe girme öncesi ve sonrası dönemdeki dış ticaretine ilişkin verilerin mukayesesi yöntemine başvurulmuştur. Kuruluşunun 100. yıl dönümü olan 2023 yılında Dünya’nın on büyük ekonomisi arasına girmeyi, 500 milyar Dolar ihracat tutarına ulaşmayı hedefleyen Türkiye’nin bu hedeflere ulaşabilmesinin birincil şartı daha fazla sanayileşme ve üretime dayalı büyümedir. Türkiye’nin söz konusu hedeflere ulaşabilmesi için serbest ticaret kanallarını genişletmesi, mevcut potansiyelini kullanarak özellikle hedef pazarlarla ticari ilişkilerini olması gereken düzeylere taşıması gerekmektedir.

According to decision No. 1/ 95 of the Turkey-EU Association Council regulating the Custom Union between EU and Turkey, Turkey has the obligation to adapt the EU’s common commercial policy. In this context, Turkey signed or is going to sign or intends to sign similar agreements on the basis of mutual benefit with third countries, which had signed preferential trade agreements with the European Union earlier. Whereas those free trade agreements Turkey is signing with third parties have the effect of boosting the trade with these countries reciprocally, the trade between Turkey and those countries with which trade negotiations are going on and are not completed yet or even have not been started yet is suffering to the very disadvantage of Turkey, giving rise to unfair competition. Free trade agreements between the EU and third countries, being not incorporated in same and similar agreements with Turkey, cause a flood of non-European goods entering Turkey via the Custom Union, custom duties being avoided due to the very terms of the Custom Union, and thus causing severe trade diversions. What is more, Turkey has to provide the same concessions as the EU has granted to third parties staying in association with the EU, according to the constraints of the Custom Union binding and obliging Turkey. Thus it is foreseeable that in near future further free trade agreements of the EU coming up or being in negation with countries not in similar trade interdependencies with Turkey, will cause further pressure, distorting the competitiveness of Turkish production and trade. As a result of the dramatic and fundamental policy changes emerging at the beginning of the last decade, Turkey is and was eager to diversify its trade structure towards multilateral foreign trade policy, so that in this scope, close partnerships and enhanced trade flow with these above mentioned North African countries and the Middle East in general is envisaged, promoted and fostered. In the context of this work, five North African countries (Egypt, Tunisia, Morocco, Libya, Algeria) are going to be elaborated with regard to their respectively bilateral trade with Turkey and vice versa. Secondly those countries among these having conducted free trade agreements with Turkey i.e. Egypt, Tunisia and Morocco, were further subject of a survey in regard to the impact of this Agreements on Turkish overall trade in general, and then in special, on the trade of Turkey with these countries respectively. The elaboration of the commercial relations of Turkey in general and in particular with these countries under study is based upon foreign trade data in comparison of then and now, i.e. data before the free trade agreements have been conducted and afterwards are compared. Turkey having set itself the goal to become one of the world’s 10 largest economies and to reach 500 billion dollars of exports volume in 2023, the centenary anniversary of the Turkish Republic, is conscious of the pre-condition that this high set target is only to be mastered by further industrialization and production-based growth. This projection necessitates of course the duty to explore, expand and deepen free trade channels wherever possible. It’s a matter of course that this work has to be handled by beginning with already existing trade relations with targetted markets of high potential aiming to boost them to their possible and potential peak.
Keywords: Dış Ekonomik İlişkiler; Dış İlişkiler; Ekonomi; Kuzey Afrika Ülkeleri; Türkiye; Türkiye --Ticaret Politikası; Uluslararsı Ticaret